Analisis Keefektifan Event Marketing Pada Pembentukan Ekuitas Merek - yoga, made sindhu (Jurnal Ilmiah Manajemen & Bisnis, 2016)
The purpose of this researchto build consumer awareness ofthe brand LA Lights and gives an overview of consumer positively to the brandLA Lights. This study was designed to analyze event marketing as an effectiveway to build LA Lights brand equity. The location of this study conducted inYogyakarta in accordance with the enterprise segments which are the consumerteenagers and independent communities.The results of research in the form ofanswers using a Likert scale was analyzed by looking at the effect of relationshipmarketing event of the formation of brand equity LA Lights by using multipleregression models. Overall, event marketing LA Lights held assessed effectivelybuild brand equity LA Lights. This happens because the market in the city ofYogyakarta is a potential market for the brand LA Lights targeting consumersteenagers and independent communities. Based on these results, the companycan continue to organize events marketing sustainably and improve the qualityof the event marketing to build brand equity LA Lights.